2020
DOI: 10.3390/ma13245787
|View full text |Cite
|
Sign up to set email alerts
|

Textile Reinforced Concrete in Combination with Improved Self-Healing Ability Caused by Crystalline Admixture

Abstract: The main aim of this study was to investigate the improved autogenous healing of concrete caused by a crystalline admixture in combination with textile reinforced concrete (TRC). This phenomenon (improved healing) has not yet been described by any independent study, and not at all in relation to TRC. The results of the study confirmed that the interaction between TRC and the crystalline admixture’s self-healing ability is advantageous and usable. The application of crystalline admixture could ensure the long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Although it was concluded in [ 35 ] that the effect of self-healing is more pronounced in concrete with higher strength, this is not confirmed here—namely, the M-0.45-CWA and M-0.55-CWA mixes have the same number of cracks healed above 90%. It is known that cracks as small as 0.1 can be healed by autogenous healing [ 16 , 37 ]. However, considering the width of cracks healed over 90%, it can be observed that a larger number of cracks healed with a width of 0.15 mm in concrete mixes with CWA than in reference concrete mixes (3 cracks with a width of 0.15 mm healed in mixes M-0.45-CWA and M-0.55-CWA, while only 1 crack healed in mixes M-0.45-R and M-0.55-R).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although it was concluded in [ 35 ] that the effect of self-healing is more pronounced in concrete with higher strength, this is not confirmed here—namely, the M-0.45-CWA and M-0.55-CWA mixes have the same number of cracks healed above 90%. It is known that cracks as small as 0.1 can be healed by autogenous healing [ 16 , 37 ]. However, considering the width of cracks healed over 90%, it can be observed that a larger number of cracks healed with a width of 0.15 mm in concrete mixes with CWA than in reference concrete mixes (3 cracks with a width of 0.15 mm healed in mixes M-0.45-CWA and M-0.55-CWA, while only 1 crack healed in mixes M-0.45-R and M-0.55-R).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the water penetration depth in concrete with incorporated CWA should be lower compared to the water penetration depth in reference concrete, which is confirmed by the authors in [ 10 , 14 ] but also disputed in [ 15 ]. As previously described, CWA also promotes self-healing of cracks [ 16 , 17 , 18 , 19 , 20 ]. The research presented in [ 18 ] implies that each CWA produces different products/crystals responsible for reducing water penetration and self-healing of concrete.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…A specimen with a specified crack width can be created in multiple ways [ 21 , 22 , 23 ]. Basically, a splitting tensile test is utilized.…”
Section: Experimental Programmentioning
confidence: 99%